Hillbilly, volume 4: red eyed witchery from beyond ebook - Powell, Eric (Hillbilly: Red Eyed Witchery From Beyond (2018), 2023)
Writer Eric Powell (The Goon) and artist Simone Di Meo (Old Man Logan) bring you the next chapter in the tale of Rondel the wandering Hillbilly. A terror from beyond the stars has descended on the hills to spread fear among the people. When Boss Krugen employs Rondel to find out what this black power has done with his lost kin, Rondel may have found an evil beyond even what the wielder of the Devil's Cleaver can handle. The fourth volume in Eric Powell's Hillbilly series promises to be the strangest yet!